Fistulococcus, a new genus of soft scale insect (Sternorrhyncha, Coccidae) proposed for two new species from Hong Kong and Papua New Guinea - Hodgson, Chris J.; Martin, Jon H. (Zootaxa, 2005)
A new genus, Fistulococcus Hodgson & Martin is introduced, to accommodate two new species of soft scale insect. All stages (except the pupa) of the type species, F. pokfulamensis from Gnetum luofuense (Gnetaceae) in Hong Kong, are described. All female stages, and the second-instar male, are described for F. intsiae from Intsia bijuga (Fabaceae, Caesalpinioideae) in Papua New Guinea. The structure of the dorsal chambered ducts is discussed in relation to the types of wax secreted. The relationship of Coccidae with plants in the Gymnospermae is discussed, as part of the account of F. pokfulamensis.